Paleoproductivity and deep-sea oxygenation in Cosmonaut Sea since the last glacial maximum: impact on atmospheric CO2 - Hu, Liangming; Zhang, Yi; Wang, Yizhuo; Ma, Pengyun; Wu, Wendong; Ge, Qian; Bian, Yeping; Han, Xibin (Frontiers in Marine Science, 2023)
The paleoproductivity in the Southern Ocean plays a crucial role in controlling the atmospheric CO2 concentration. Here, we present the sediment record of gravity core ANT37-C5/6-07, which was retrieved from the Cosmonaut Sea (CS), Indian Ocean sector of the Southern Ocean. We found that the change in the oxygen concentration in the CS bottom water is strongly correlated with the atmospheric CO2 fluctuations since the Last Glacial Maximum (LGM). Based on the change in the export production, we reconstructed the evolution history of the deep-water ventilation/upwelling in the study area. During the LGM, a large amount of respiratory carbon was stored in the deep Southern Ocean due to the effect of the low export productivity and restricted ventilation. The oxygen concentration was also low at this time. Despite the increase in paleoproductivity, the biological pump efficiency remained at a low level during the Last Deglaciation. Vast quantities of CO2 were released into the atmosphere through enhanced upwelling. The recovery of ventilation during this period facilitated the supply of oxygen-rich surface water to the deep ocean. Moreover, signals were identified during the transitions between the Heinrich Stage 1 (HS1), Antarctic Cold Reverse (ACR), and Younger Drays (YD) periods. During the Holocene, the productivity increased overall, and the oxygen in the bottom water was consumed but still remained at a high level. This may have been caused by the enhanced ventilation and/or the prevalence of East Cosmonaut Polynya (ECP) near Cape Ann.